PENGARUH GREEN MARKETING DAN STORE ATMOSPHERE TERHADAP PURCHASE DECISION DI RESTORAN FAST FOOD - Amalia Putri Wiguna; Vera Desy Nurmalia (FE Program Studi Manajemen, 2022)
This study aims to determine how much influence green marketing and store atmosphere have on purchasing decisions in the millennial generation at global fast food restaurants in Indonesia. The problem in this study is the existence of a new policy carried out by fast food restaurants to reduce plastic waste through the green marketing process. In addition to this, the millennial generation of consumers who come to fast food restaurants not only enjoy the food served but also to enjoy the restaurant atmosphere (store atmosphere).This research uses multiple linear regression method. The results of the analysis show that green marketing partially has a positive and significant effect on purchasing decisions, where the t-test significance value is 0.020 (<0.05) and the regression coefficient has a positive value of 0.188. Store atmosphere partially positive and significant effect on purchasing decisions, where the significance value of the t-test is 0.005 (<0.05) and the regression coefficient has a positive value of 0.255.Keywords: Green Marketing, Store Atmosphere, Purchase Decision.